Can Distributed Ledger Technologies Promote Trust for Charities? A Literature Review - Christie, Andrea (Frontiers in Blockchain, 2020)
This paper presents a literature review on the role of the distributed ledger technology in promoting stakeholder trust for charitable organizations. The purpose of this review is to capture existing knowledge on the relationship between the following key variables: charity, trust and accountability, and distributed ledger technology—with emphasis on blockchain technology as a primary example of this technology. After shortlisting the discovered literature pool to 35 papers, the following three themes were identified. The first theme presents the various definitions of key concepts in crypto-philanthropy literature. The second theme captures existing views on why stakeholder trust is declining in charitable conduct. These views include: (1) organizational boundary shifts; (2) monitory complexity; and (3) poor regulatory design. The third and final theme presents a hypothesis on how the distributed ledger technology can promote trust for charities. The technology is hypothesized to promote trust by drawing on the following three elements: (1) decentralization; (2) provenance; and (3) rule-enforcement. A number of shortcomings are then highlighted in the literature pool. The first shortcoming pertains to the inconsistent treatment of key concepts in crypto-philanthropy studies. The second shortcoming pertains to the lack of discussion on whether the distributed ledger technology may potentially decrease stakeholder trust if implemented irresponsibly by charities. In conclusion, a series of future research pathways are provided. These recommendations include: (1) clarifying key concepts; (2) suggesting “crypto-philanthropy” as a formal disciplinary title; (3) highlighting under-researched areas; and, (4) recommending strategies for building a new crypto-philanthropic theory. From an academic perspective, the findings contribute to literature by bridging the gap between crypto-economic, institutional governance and non-profit accountability theories. The findings may also guide charity managers, regulators and policy-makers in understanding the capacities of the distributed ledger technology in legitimizing charitable conduct.